2009
DOI: 10.1080/01421590802637958
|View full text |Cite
|
Sign up to set email alerts
|

A game for teaching antimicrobial mechanisms of action

Abstract: The game could be applied to other undergraduate courses in the field of Health Sciences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 13 publications
1
45
0
1
Order By: Relevance
“…Valente and colleagues used a board game to teach the mechanisms of antimicrobial actions. 8 Girardi and colleagues created a "T-and B-Cell Ontogeny" board game. 9 In both studies, students who played the game had positive impressions of the game and showed improvement between pretest and posttest scores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Valente and colleagues used a board game to teach the mechanisms of antimicrobial actions. 8 Girardi and colleagues created a "T-and B-Cell Ontogeny" board game. 9 In both studies, students who played the game had positive impressions of the game and showed improvement between pretest and posttest scores.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] Not only can games make learning more enjoyable, but they can also encourage in-class participation and improve students' attitudes toward learning the material. The type of game and the methods of analysis seem dependent on the type of content and the end educational goal of the game.…”
Section: Introductionmentioning
confidence: 99%
“…Most teachers agree that students potential of learning from a didactic lecture is less when compared to students who are engaged in a learning process where they critically analyze the problem, acquire the knowledge and able to apply it in a meaningful and applicable way [7].…”
Section: Discussionmentioning
confidence: 99%
“…Using the above material, we introduced the teams to a game with two tasks to reinforce the core concepts of PBL followed at RAKMHSU and to promote imagination, problem designing, problem solving skills, confidence, and team working spirit. "Game based learning," as it is called, is an instructional methodology in which the learner participates in a competitive game with preset rules [6,7]. It has been proven to have better attitude, team spirit, and retention rates than the traditional didactic methods.…”
Section: Introductionmentioning
confidence: 99%
“…The "innovative" teaching strategies such as gaming, respond to different learning styles (visual, auditory, or kinesthetic) of students and facilitates learning by making the learning process more exciting and entertaining [5]. Many studies have considered educational gaming as more entertaining and motivating for students [3,5,6,11,14,22,23]. The learning process involves not only the internalization of the knowledge, but also the emotional and social satisfaction of the learner.…”
Section: Discussionmentioning
confidence: 99%